Aplicación del proceso contable en la constructora del ing. Tony Alberto Cisneros Merino de la ciudad de Loja, periodo: julio a diciembre del 2014. - Gonzaga Pereira, Paula Anabel (2016)
This research paper entitled "APPLICATION OF ACCOUNTING PROCESS IN THE CONSTRUCTION OF ING. TONY CISNEROS ALBERTO MERINO LOJA CITY, PERIOD: JULY TO DECEMBER 2014.", has been prepared as a requirement prior to choose the degree of Engineer in Accounting and Auditing, Certified Public Accountant Auditor, established in Regulation Academic Regime National University of Loja, and as a proposal for the construction "CISNEROS". To comply with the general objective: Apply the accounting process in the Construction of Mr. Tony Alberto Cisneros Merino city of Loja, period. July to December 2014, it proceeded to carry out the plan and manual accounts in accordance with the requirements and needs of the construction, with the development of the accounting process, this is main and auxiliary books financial statements were obtained, providing true and timely information, the accounting record was made on the basis of the accounting and tax rules introduced for the construction. Upon completion of this work will be given to Ing. Tony Cisneros Merino, economic and financial information timely and real, accounting process that was applied considering the accounting and tax rules, recommending continue its application because it allows you to have real data and comply as established by the regulatory agencies.